Exploring options for a universal old age pension in Tanzania Mainland - Twahir Khalfan; Elineema Kisanga; Vincent Leyaro; Faith Masekesa; Michael Noble; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The provision of a universal old age pension is increasingly recognized as an important instrument for strengthening and extending social protection. A growing number of emerging economies, including East African countries, are introducing universal old age pensions to guarantee at least a basic level of social security. However, such a benefit has not been established in Tanzania Mainland, and a lack of adequate financing is viewed as one of the main constraints. This paper employs a data set from Tanzania-the Household Budget Surveys-and applies a taxbenefit microsimulation model for Tanzania (TAZMOD) to explore possible options for designing and financing a universal old age pension in Tanzania Mainland. The findings of this paper present evidence on reform scenarios and financing options that could be adopted by Tanzania Mainland to establish and sustain a universal old age pension.
Keywords: H55; I38; J14; 330; microsimulation; old age; public pensions; social security; Tanzania